p-3q=2

Simple and best practice solution for p-3q=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p-3q=2 equation:


Simplifying
p + -3q = 2

Solving
p + -3q = 2

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '3q' to each side of the equation.
p + -3q + 3q = 2 + 3q

Combine like terms: -3q + 3q = 0
p + 0 = 2 + 3q
p = 2 + 3q

Simplifying
p = 2 + 3q

See similar equations:

| 3x+8x=3x-5 | | 3p-7=3p+11 | | 4x+4+4x+4x+3=180 | | 4=k+8 | | -3x^2-24x+36=10 | | 3x+y=51 | | 3x^2+3y^2+3z^2-x+6y+3z=9 | | (u-3)(u+4)= | | -3x^2-24x+12=10 | | (2y-7)=(14-2)+4y | | ((5^(-1/2))*(5x^(5/2)))/(5x)^(3/2) | | y=-5/7x | | 1/10x^3-15/2-25 | | 8-2(4-1)= | | x^2-2xy+y^2-6x-6y-1=0 | | 8x+4(-2x-1)=-4 | | x^2+2xy+y^2-6x-6y-1=0 | | 1/2x-5/6=2x-3/4 | | 64.5x/6-3x/4=x-11 | | q-p=6 | | 2x-4=5+6x | | (Y)=7 | | 9p+3q=-2 | | 3z+6(z+3)-10= | | 4y+4y=-16 | | F(4z)=3x^2+4 | | X+2X+2=4 | | h=1.5+8.4t+-4.9t^2 | | 6y-3(y+4)+3(y-6)= | | 4*3/10 | | 3(4a-8)+12= | | 8x+4(-2X+1)=-4 |

Equations solver categories